2019
DOI: 10.2147/jir.s210441
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epac1 inhibits PKR to reduce NLRP3 inflammasome proteins in retinal endothelial cells</p>

Abstract: Purpose: Inflammation has been strongly associated with retinal damage in diseases such as diabetic retinopathy. Several studies have reported that high glucose exposure induces damage to the retinal vasculature. We and others have shown that high glucose can activate the NOD-like receptor family, pyrin domain containing family member 3 (NLRP3) pathway, leading to increased levels of cleaved caspase 1 and IL-1β to activate a number of inflammatory pathways in the retina. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…PKR inhibition has been shown to decrease inflammation and attenuate lung injury in LPS-challenged mice [ 12 , 13 ]. The present in vitro study showed that inhibition of PKR exerted a protective effect through regulation of inflammatory response in macrophages and in retinal endothelial cells [ 8 , 25 ]. The imidazolo-oxindole derivative C16 is the first selective and potent PKR inhibitor to be described.…”
Section: Discussionmentioning
confidence: 99%
“…PKR inhibition has been shown to decrease inflammation and attenuate lung injury in LPS-challenged mice [ 12 , 13 ]. The present in vitro study showed that inhibition of PKR exerted a protective effect through regulation of inflammatory response in macrophages and in retinal endothelial cells [ 8 , 25 ]. The imidazolo-oxindole derivative C16 is the first selective and potent PKR inhibitor to be described.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of SC 79 was selected by our preliminary tests (data not shown). The concentrations of ZLN005, C16, Pifithrin-μ and mito TEMPO were referred from published studies [23,24,25,26]. Anti-p38, anti-p-p38, anti-p53, anti-p-p53, anti-AKT, anti-p-AKT, anti-PGC-1α, and anti-β-actin were all bough from Cell Signaling Technology (Danvers, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial cells line the retinal microvasculature and comprise the highly selective inner BRB ( 65 ). NLRP3/caspase-1 activation and IL-1β release have been recorded in retinal endothelial cells (RECs) in various in vivo and in vitro models of DR ( 42 , 43 , 67 ). Pyroptotic cell death and caspase-1 activity were markedly increased in human retinal microvascular endothelial cells (HRMECs) incubated in 30 mM high glucose compared to controls ( 44 ).…”
Section: Role Of Pyroptosis In Retinal Diseasementioning
confidence: 99%